Improving the Social Inclusion of Mobility Impaired Users - Pires, C.; Pinto, F.; Rodrigues, E. M.; Dias, J. (Proc. of the Social Mobile Web 2010 Workshop (at the 12th International Conference on Human-Computer Interaction with Mobile Devices and Services, MobileHCI 2010), 2010)
In this paper we present a study with a group of mobility impaired individuals (paraplegic and quadriplegic). The goal of the study was to unveil usability issues with current user interfaces and to derive design recommendations towards the development of future mobility impaired-oriented user interfaces that facilitate an integrated access to several communication and social media services in a unified user experience. We focused our analysis on hardware interfaces, considering modalities beyond the more traditional keyboard and mouse, like touch or speech interaction, and on specific computer-mediated communication software interfaces for services such as email, agenda, audio and video conferencing, and social media services. Our study revealed that multimodal interfaces, in particular those that include the speech modality, may help overcome observed interaction difficulties both on the mobile and desktop platforms